Te role of disturbances of the psychosexual spherein schizophrenia in diagnosing of paraphilias - L. Yu. Demidova; G. E. Vvedensky; T. E. Makarova; M. Yu. Kamenskov; L. N. Shtark (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Te article is concerned with the study of disturbances in psychosexual sphere, which are specifc for schizophrenia spectrum disorders. Te results of a comparison of two groups are presented: 29 people were diagnosed with schizophrenia and schizotypal disorder and a comparison group of 34 people without endogenous pathology. Te study outcomes of their gender self-consciousness with methods «MF», «CTAT», «Coding» are shown that the presence of endogenous disorder changes the psychosexual profle of patients on a number of signs. Persons with schizophrenia and schizotypal disorder, regardless of their comorbide diagnosis of paraphilia are characterized by lower value of masculinity, high distinction with the male role, absence of intention to line up with the man-image, in some cases instability of identity, altered emotional attitudes to sex-role stereotypes, emotional ambivalence.